The Comparison of Think Talk Write and Think Pair Share Model with Realistic Mathematics Education Approach Viewed from Mathematical-Logical Intelligence - Himmatul Afthina; Mardiyana Mardiyana; Ikrar Pramudya (Universitas Sebelas Maret, 2017)
The aims of this research to determine the effect of Think Talk Write (TTW) and Think Pair Share (TPS) model with Realistic Mathematics Education (RME) approach viewed from mathematical-logical intelligence. This research employed the quasi experimental research. The population of research was all students of the eight graders of junior high school in Karangamyar Regency in academic year 2016/2017. The result of this research shows that (1) TTW with RME approach gave better mathematics achievement than TPS with RME approach, (2) Students with high mathematical-logical intelligence can reach a better mathematics achievement than those with average and low, whereas students with average mathematical-logical intelligence can reach a better achievement than those with low one, (3) In TTW model with RME approach, students with high mathematical-logical intelligence can reach a better mathematics achievement than those with average and low, whereas students with average and low mathematical-logical intelligence gave same mathematics achievement, and in TPS model with RME approach students with high mathematical-logical intelligence can reach a better mathematics achievement than those with average and low, whereas students with average mathematical-logical intelligence can reach a better achievement than those with low one (4) In each category of mathematical-logical intelligence, TTW with RME approach and TPS with RME approach gave same mathematics achievement.